A Sex Comparison of Fall and Fracture Occurrence in the Elderly Diabetic Population: A Quantitative Study - Fahamina Ahmed; Kaylin Miller; Meva Beganovic; Ali Siddiqui; Candice Smith (Women's Health Reports)
Aims: To assess differences in falls and fractures in men and women with type 2 diabetes mellitus (T2DM) within a diverse population in Southeast Louisiana. Methods: A list of 1200 patients was generated through an electronic health record system using keywords: diabetic diagnosis, falls, and fractures to conduct this retrospective cohort study. This chart review included adults with T2DM who experienced at least one fall and/or fracture between January 2018 and May 2023 at East Jefferson General Hospital located in Metairie, Louisiana. Only falls and fractures that resulted in a hospital visit were included. Results were compared between males and females. Results: Patient data were collected from 100 randomly selected patients: 50 females and 50 males (mean age 67 years, 97% of patients were non-Hispanic, and 72% Black). Statistical analysis was conducted using the Student’s t test, Fisher’s exact, and Pearson correlation. An average of 3–4 falls occurred per patient, with no significant sex difference observed (p = 0.97). Thirty-eight percent of patients experienced a fracture with a significant sex difference (50% of female vs. 26% of male patients [p = 0.02]). Positive correlations between comorbid conditions and falls and fractures were seen, particularly in women: a moderate correlation for falls (r = 0.48, p < 0.01) and a strong correlation for fractures (r = 0.52, p < 0.01). Patients not on insulin treatment experienced a greater occurrence of fractures than insulin-dependent patients (46% vs. 22%, p = 0.03). Conclusions: Our findings suggest that in a diverse population, women with T2DM are at an increased risk of experiencing fractures, and specialized care should be given to this population to reduce the risk of fracture occurrence. Additional comorbidities increase the risk of falls and fractures.